Organophosphine‐Sandwiched Copper Iodide Cluster Enables Charge Trapping. Issue 47 (18th October 2021) - Zhang, Jing; Xie, Mingchen; Xin, Ying; Han, Chunmiao; Xie, Linghai; Yi, Mingdong; Xu, Hui
Abstract: Herein, we report a feasible molecular design of the binuclear clusters featuring the n‐p‐n heterojunction of biligand‐sandwiched inorganic units, which can be used as the effective charge trapper in ambipolar transistor memories with the large memory windows and the energy‐saving operation. We found that the hole confinement on the p‐type inorganic units is enhanced by spatial electronic anisotropy provided by the peripheral n‐type organic phosphine ligands. The steric hindrance of the coordination sites, the insulating effect of the carbon‐phosphorous single bonds and the parallel dual‐ligand coordination mode jointly elongate the interunit distances to nanometer scale and restrain the intramolecular electronic communications, leading to the tunable and reliable charge trapping. Our results show that the spatial effect is crucial to further amplifying the electronic differences between organic and inorganic units for function enhancement. Abstract : Molecular n‐p‐n heterojunction based on biligand‐sandwiched copper iodide nanocluster is constructed as charge trapper in ambipolar transistor memories featuring large memory windows and energy‐saving operation. Spatial electronic anisotropy of the lamellar structure and steric and insulating effects of phosphine ligands effectively hinder intramolecular electronic communications, leading to the tunable and reliable charge trapping as a basis of real single‐molecule devices.